Efficacy and safety of extracorporeal membrane oxygenation combined with continuous renal replacement therapy in the management of pediatric acute respiratory distress syndrome - Yang, Yufan; Wang, Xiangni; Lu, Xiulan; Zhang, Xinping; Huang, Jiaotian; Xiao, Zhenghui (Frontiers in Pediatrics, 2025)
BackgroundThe efficacy and safety of combining extracorporeal membrane oxygenation with continuous renal replacement therapy remain controversial. This study aimed to evaluate the efficacy and safety of extracorporeal membrane oxygenation combined with continuous renal replacement therapy in the treatment of pediatric acute respiratory distress syndrome.MethodsThis retrospective study, conducted at Hunan Children's Hospital between January 2019 and December 2023, included 30 pediatric patients with acute respiratory distress syndrome who underwent extracorporeal membrane oxygenation treatment. The patients were divided into two groups based on whether continuous renal replacement therapy was used during treatment: 21 in the extracorporeal membrane oxygenation with continuous renal replacement therapy group and nine in the extracorporeal membrane oxygenation-only group. The groups were compared using t-test or Wilcoxon rank-sum test.ResultsThis study included 19 (63.3%) male and 11 (36.7%) female patients (mean age: 63.33 ± 54.41 months). The ratios of arterial partial pressure of oxygen to fraction of inspired oxygen before and at withdrawal of extracorporeal membrane oxygenation were 58.50 (40.75–70.31) and 257.00 (113.25–358.33) mmHg, respectively (P < 0.05). In the extracorporeal membrane oxygenation with continuous renal replacement therapy group, 21 patients (70.0%) underwent continuous renal replacement therapy, including those with acute renal injury (n = 5), fluid overload (n = 13), hyperkalemia (n = 3), and removal of inflammatory mediators (n = 3), and improvement was observed.ConclusionsThe combination of extracorporeal membrane oxygenation and continuous renal replacement therapy provides safe and effective respiratory support for pediatric patients with severe acute respiratory distress syndrome and enables effective fluid-balance management, removal of inflammatory factors, and maintenance of electrolyte equilibrium.